Analisis Timbulan, Densitas, dan Komposisi Sampah Pasar Bojonegoro Kabupaten Bojonegoro - Afrianisa, Ro'du Dhuha; Pramestyawati, Talent Nia; Putri, Aulia Irkhamni (Jurnal EnviScience (Environment Science), 2023)
Bojonegoro market is a type A traditional market where there is high trading activity in Bojonegoro. Buying and selling activities at the Bojonegoro market cause leftovers to be generated every day. The remaining activities in the form of solids or what is called waste will affect the generation that occurs. The purpose of this study is to determine the generation data, density and composition of Bojonegoro Market waste. The method used is descriptive quantitative by calculating waste generation. Garbage measurement and sampling activities were carried out for eight consecutive days in accordance with SNI 19-3964-1994 reference. The results showed that the Bojonegoro market waste generation was 146 kg/day with a density value of 210 kg/m3. The composition of the top three is dominated by coconut shell waste of 78.3 kg/day, vegetable waste of 11.2 kg/day, and fruit waste of 8.4 kg/day.